MILITARY AND REGIMENTAL CHURCHES OF THE DON COSSACKS AND THEIR ROLE IN THE SPIRITUAL GUIDANCE OF THE COSSACKS IN THE XVIII - EARLY XX CENTURIES - Anatoly Agafonov (Гуманитарные и юридические исследования)
As a result of the inclusion of the land of the Don Army in the state-legal space of Russia, the Cossacks were subject to the basic Imperial principles and requirements of the Church organization and military administration, as part of the spiritual and moral policy of the state. The article examines the main directions of church-temple construction and formation of military and regimental clergy, taking into account the peculiarities of development of the Cossacks, its transformation into a military-serving class. The author concludes that the government and Synod policies in the XVIII - early XX centuries resulted the establishment of the Church life in the land of the Don Cossacks, including a coherent system of diocesan administration and the formation of the clergy, the construction and operation of churches, temples and monasteries. Military temples often served as regimental churches for Cossack regiments serving in the area of the Don Army. The Don regimental churches and regimental clergy were formed on the same conditions as those in the Russian regular army, but had some differences due to the peculiarities of the call, formation, deployment of regiments, and the performance of service by the Cossacks. Military and regimental churches were the centers of education, spiritual care and education, the keepers of military trophies and Museum relics, historical traditions of the Cossacks.